INOVASI BAKSO PENTOL DAUN KELOR (MORINGA OLEIFERA) TERHADAP SELERA MAKAN PADA ANAK SEBAGAI UPAYA PENCEGAHAN DAN PENANGANAN STUNTING - Simatupang, Lenny Lusia; Hutahaean, Masta Melati (UNIVERSITAS SARI MUTIARA INDONESIA, 2024)
The acceleration program for improving nutrition in Indonesia is an effort to achieve the Sustainable Development Goals (SDG's). Moringa oleifera Lam (known as Kelor) is a plant that has extraordinary nutritional and therapeutic properties. Globally considered a food that has the potential to eradicate malnutrition and contributes significantly to preventive health care. The purpose of this study was to determine the effect of giving meatballs made from moringa leaves on increasing body weight and appetite in children in Cinta Rakyat Village. The research method was a quasi-experimental study with a Completely Randomized (CRD) using a One group pre-test and post-test design with a control group. Research Results The provision of moringa leaf intervention appeared to have an effect on the appetite and weight gain of toddlers after being given additional meatballs made from moringa leaves on the daily menu for 90 days.